PARADIGMA ISLAM DAN TRANSFORMASI SOSIAL (STUDI PEMIKIRAN KUNTOWIJOYO) - Sidik Ibrahim (Hunafa: Jurnal Studia Islamika, 2005)
Kuntowijoyo is one of Indonesian intellectuals who is very concerned with the teachings of Islam in the context of sosial change. According to him, the Quran can be made as paradigm which is called Islamic paradigm. This Islamic paradigm is intended to formulate social theories of typical Islam which is called social prophetic science. The intended paradigm is mode of thought, mode of inquiry resulting in mode of knowing. By this paradigm the Quran is expected to be science construction from which we can comprehend the reality as the Quran comprehends it.Kata Kunci: Pradigma Islam, Transformasi Sosial